Minimally Invasive versus Conventional Aortic Valve Replacement: A Propensity-Matched Study from the UK National Data. Issue 1 (January 2016) - Attia, Rizwan Q.; Hickey, Graeme L.; Grant, Stuart W.; Bridgewater, Ben; Roxburgh, James C.; Kumar, Pankaj; Ridley, Paul; Bhabra, Moninder; Millner, Russell W. J.; Athanasiou, Thanos; Casula, Roberto; Chukwuemka, Andrew; et al.
Objective: Minimally invasive aortic valve replacement (MIAVR) has been demonstrated as a safe and effective option but remains underused. We aimed to evaluate outcomes of isolated MIAVR compared with conventional aortic valve replacement (CAVR). Methods: Data from The National Institute for Cardiovascular Outcomes Research (NICOR) were analyzed at seven volunteer centers (2006–2012). Primary outcomes were in-hospital mortality and midterm survival. Secondary outcomes were postoperative length of stay as well as cumulative bypass and cross-clamp times. Propensity modeling with matched cohort analysis was used. Results: Of 307 consecutive MIAVR patients, 151 (49%) were performed during the last 2 years of study with a continued increase in numbers. The 307 MIAVR patients were matched on a 1:1 ratio. In the matched CAVR group, there was no statistically significant difference in in-hospital mortality [MIAVR, 4/307, (1.3%); 95% confidence interval (CI), 0.4%-3.4% vs CAVR, 6/307 (2.0%); 95% CI, 0.8%-4.3%; P = 0.752]. One-year survival rates in the MIAVR and CAVR groups were 94.4% and 94.6%, respectively. There was no statistically significant difference in midterm survival (P = 0.677; hazard ratio, 0.90; 95% CI, 0.56–1.46). Median postoperative length of stay was lower in the MIAVR patients by 1 day (P = 0.009). The mean cumulative bypass time (94.8 vs 91.3 minutes; P = 0.333) and cross-clamp time (74.6 vs 68.4 minutes; P = 0.006) were longer in the MIAVR group; however, this was significant only in the cross-clamp time comparison. Conclusions: Minimally invasive aortic valve replacement is a safe alternative to CAVR with respect to operative and 1-year mortality and is associated with a shorter postoperative stay. Further studies are required in high-risk (logistic EuroSCORE > 10) patients to define the role of MIAVR.